Use of physical activity and cardiorespiratory fitness in identifying cardiovascular risk factors in male brazilian adolescents - Lilian Messias Sampaio Brito; Luis Paulo Gomes Mascarenhas; Deise Cristiane Moser; Ana Cláudia Kapp Titski; Monica Nunes Lima Cat; Manuel João Coelho-; Margaret Cristina da Silva Boguszewski; Neiva Leite (Universidade Federal de Santa Catarina, 2016)
The aim of this study was to investigate the impact of physical activity (PA) and cardiorespiratory fitness (CRF) levels on the prevalence of overweight and high blood pressure levels in adolescents. In this observational, cross-sectional study, 614 boys aged 10-14 years were assessed for height, body mass, body mass index (BMI), waist circumference (WC) and blood pressure (BP). CRF was assessed using a run test (Léger Test) and subjects were then grouped according to their CRF level. PA level was assessed through a questionnaire (The Three Day Physical Activity Recall) and classified into two groups, namely > 300 minutes of PA/week and < 300 minutes of PA/week. Maturational stage was evaluated according to the development of pubic hair (self-assessment) as proposed by Tanner. We used statistical descriptive analysis, univariate and multivariate analyses in the total participants and subjects were divided by age. Fifty percent of the sample performed < 300 minutes of PA/week and 67.6% had unsatisfactory CRF levels. There was a higher prevalence of unsatisfactory CRF levels among subjects with altered BMI (overweight), WC (abdominal obesity) or BP (high blood pressure) for all age groups. PA history, however, did not show any significance. A total of 31% of participants were overweight, 24.8% had abdominal obesity and 15.4% had increased BP. Unsatisfactory CRF levels were found to be a better predictor for the diagnosis of cardiovascular diseases (CV) risk factors than PA history, regardless of age group.